A Case of Humeral Head Fracture-dislocation with Vascular Injury: How We Managed it - K Meenakshisundaram; Nagesh C Sangolgi; Kandaswamy K G; Hari Sivanandan; Athipathi Sundararaj; Chiranjeevi K P (Journal of Orthopedics and Joint Surgery)
Axillary artery injury is uncommon, although proximal humerus fractures are prevalent. The majority of axillary artery injuries in the literature have been attributed to anterior glenohumeral dislocation; a few have been linked to single proximal humerus fractures or fracture-dislocation. The axillary artery is vulnerable to injury because of a proximal humerus fracture due to its anatomical placement. Due to the quantity of collateral circulation in the upper limbs, vascular damage may occur even though the radial pulse is perceptible. The most common vascular injury produced by a proximal humerus fracture was an intimal rupture with subsequent thrombosis because there are no palpable peripheral pulses and no ischemia, axillary artery injury often goes undiagnosed at first, putting the hand at risk of necrosis and amputation if ischemia persists, and the forearm at risk of compartment syndrome after revascularization. A comprehensive physical examination, as well as a low threshold for Doppler tests or angiography, can diagnose axillary artery injury. Although the vascular insult resolves spontaneously, it is vital to recognize the link between such fractures and vascular injuries in order to diagnose them early and avoid major complications, such as amputation. We provide a case of axillary artery injury associated with proximal humerus fractures to show the risk of axillary artery injury in the setting of proximal humerus fractures.